2021
DOI: 10.1101/2021.12.10.21267408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adolescent vaccination with BNT162b2 (Comirnaty, Pfizer-BioNTech) vaccine and effectiveness against COVID-19: national test-negative case-control study, England

Abstract: Adolescents in the UK were recommended to have their first dose of mRNA vaccine during a period of high community transmission due to the highly transmissible Delta variant, followed by a second dose at an extended interval of 8-12 weeks. We used national SARS-CoV-2 testing, vaccination and hospitalisation data to estimate vaccine effectiveness (VE) using a test-negative case-control design, against PCR-confirmed symptomatic COVID-19 in England. VE against symptomatic disease increased to 80% within two weeks … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 13 publications
(28 reference statements)
6
33
0
Order By: Relevance
“…Vaccine effectiveness above 90% against the Delta variant 7-62 days after the second dose is in line with results from other studies among adolescents in England, Israel, and USA even though different study designs were used (6,9,10). A reduced effectiveness of the mRNA vaccines against infection with the Omicron variant compared to the Delta variant has been documented in several preprint studies, primarily in adults (14-16), but also in one preprint study in adolescents in England (9).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Vaccine effectiveness above 90% against the Delta variant 7-62 days after the second dose is in line with results from other studies among adolescents in England, Israel, and USA even though different study designs were used (6,9,10). A reduced effectiveness of the mRNA vaccines against infection with the Omicron variant compared to the Delta variant has been documented in several preprint studies, primarily in adults (14-16), but also in one preprint study in adolescents in England (9).…”
Section: Discussionsupporting
confidence: 88%
“…Vaccine effectiveness above 90% against the Delta variant 7-62 days after the second dose is in line with results from other studies among adolescents in England, Israel, and USA even though different study designs were used (6,9,10). A reduced effectiveness of the mRNA vaccines against infection with the Omicron variant compared to the Delta variant has been documented in several preprint studies, primarily in adults (14-16), but also in one preprint study in adolescents in England (9). In our study we found no protective effect after one dose, but the study from England among adolescents estimated that vaccine effectiveness against symptomatic Omicron infection after one dose peaked at 50% in days 14-20 after vaccination among 12-15-year-olds and at 53% in days 21-27 after vaccination among 16-17-year-olds.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10] Compared to children 12-17 years, who receive two 30g doses, less is known known about real-world vaccine effectiveness against infection and hospitalization effectiveness for children 5-11 years, who receive two 10g doses, particularly after the Omicron variant's emergence. 11,12 We examined the effectiveness of vaccination during the Omicron variant surge that began in early December 2021 on infection and hospitalization among children 5-11 years compared to 12-17 years using NYS statewide surveillance systems.…”
Section: Introductionmentioning
confidence: 99%